O poranduba do futuro: o consumo de histórias e a imaginação cívica ribeirinha - Matias, Luis Guilherme Silva (2024)
To create a better world, it is necessary to first be able to imagine how it might be. This study aims to investigate how the consumption of stories from the Tumbira Community (AM) influences their views of possible social, cultural, economic, and political futures. In other words, it seeks to understand the role of narratives in the civic engagement of riverside people. Using the concept of civic imagination, the approach of Consumer Transformative Research, and ideas from authors and thinkers from the Global South, the research is centered on the role of narratives in civic engagement, analyzing their distinct stories and future perspectives as residents of a community that, in the last decade, has shifted from relying on timber extraction to dedicating itself to sustainable ecotourism. Ethnographic-inspired methods were employed for two field immersions, coupled with 14 semi-structured interviews and other documents, to help create a portrait of the role of narratives in the empowerment and civic engagement process. The results point to a predominance of lived stories among community members, especially about misadventures in nature and encounters with the so-called “supernatural.” The appreciation of local narratives is changing, now incorporating “outside” discourses into future visions, bringing with them the value of enterprise, tourism, and sustainability. Meanwhile, people more involved with tourism are also seen as the most engaged in the community’s public life, reaffirming the dominance of a singular vision of the future in the area. The diversity of stories proves to be an essential element in imagining different futures and promoting greater harmony in the present.